2008
DOI: 10.1002/prot.21954
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the protein structure and protein dynamics

Abstract: Recently, we have developed a method (Shih et al., Proteins: Structure, Function, and Bioinformatics 2007;68: 34-38) to compute correlation of fluctuations of proteins. This method, referred to as the protein fixed-point (PFP) model, is based on the positional vectors of atoms issuing from the fixed point, which is the point of the least fluctuations in proteins. One corollary from this model is that atoms lying on the same shell centered at the fixed point will have the same thermal fluctuations. In practice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Here, we further compare RSA profiles with theoretical thermal fluctuations computed by two methods, the Protein-fixed-point (PFP) model (Shih et al, 2007;Lu et al, 2008) and Weighted-contact number (WCN) model . These two models are shown to be able to reproduce B-factor from protein structure.…”
Section: Comparison Between Theoretical Thermal Fluctuation and Actuamentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we further compare RSA profiles with theoretical thermal fluctuations computed by two methods, the Protein-fixed-point (PFP) model (Shih et al, 2007;Lu et al, 2008) and Weighted-contact number (WCN) model . These two models are shown to be able to reproduce B-factor from protein structure.…”
Section: Comparison Between Theoretical Thermal Fluctuation and Actuamentioning
confidence: 99%
“…The relationships between thermal fluctuation and some concepts related to ASA have been studied. B-factor has shown to correlate to local packing densities (Halle, 2002), atomic distance to protein center-of-mass (Shih et al, 2007;Lu et al, 2008) and residue depth (Zhang et al, 2009). Residue flexibility was known to be correlated to its ASA in single protein (Sheriff et al, 1985) or small dataset (Carugo & Argos, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Hwang and co-workers (Shih, Huang et al 2007;Lu, Huang et al 2008) showed that the correlation matrix C is well approximated by…”
Section: The Protein Fixed-point Modelmentioning
confidence: 99%
“…ENM has recently become a popular tool to analyze protein dynamics (Zheng, Brooks et al 2007;Yang, Song et al 2009;Zheng & Thirumalai 2009). Recently, Hwang and co-workers (Shih, Huang et al 2007;Huang, Shih et al 2008;Lin, Huang et al 2008;Lu, Huang et al 2008) developed even simpler models to calculate the correlations between the atomic fluctuations in p r o t e i n s d i r e c t l y f r om their structures without using mechanical models, or performing energy minimization or matrix 56 diagonalization. They are the Protein Fixed-Point Model and the Weighted Contact Number Model, which will be discussed in the next sections.…”
Section: Elastic Network Modelmentioning
confidence: 99%
See 1 more Smart Citation